Pembuatan Buku Saku untuk Mewujudkan Wisata Beretika di Kawasan Adat Gunung Hauk Kabupaten Balangan - Bahari, Siti Hanifah; Hidayah, Sri; Nailah; Rima; Lestiani, Devi; Jamil, Achmad; Nurmasjida, Giska; Inayah, Alya Noor; Inayati, Rahmah; Haris, Ahmad Abdul; Ramelan, Ampri Wahlul; Hairin, Muhammad; Tindaon, Entry Welny (Prodi Sosiologi FISIP ULM, 2025)
The village of Ajung in Balangan Regency has great potential for nature and cultural tourism, especially on Mount Hauk, which is revered by the Dayak Pitap community. However, this potential has not been optimally managed due to frequent cultural clashes between tourists and the local community. The main problem is the lack of comprehensive written information about customs and restrictions, resulting in many tourists unintentionally violating sacred norms. This has the potential to damage the environment and cultural values that have been preserved for generations. The proposed solution is to compile a Mount Hauk Tourist Pocket Book as an official guide for tourists. This community service activity was carried out for 40 days, from July 21 to August 29, 2025, in Ajung Village. The implementation method used a participatory approach through live-in, participatory observation, in-depth interviews, and Focus Group Discussions (FGD) to ensure the active involvement of the community in each stage. The result of this activity was the creation of the Gunung Hauk Tourism Pocket Book in print and digital form, which contains an area profile, tourism rules, customary prohibitions, and practical climbing information. This output contributes to increasing tourist understanding, strengthening sustainable tourism management, and minimizing the potential for cultural conflict. Overall, this community service successfully created an ethical tourism guide model based on local wisdom that can serve as an example for the management of similar destinations.